PEMBERIAN BRAIN GYM EXERCISE DAPAT MENINGKATKAN FUNGSI KOGNITIF PADA LANJUT USIA - Hukmiyah, A. Nurul; Bachtiar, Farahdina; Leksonowati, Sri Saadiyah (UI Scholars Hub, 2019)
Aging is always accompanied by changes in all systems in the human body, including a decrease in cognitive function. Brain gym is one of exercises that can improve cognitive function in the elderly. This study aims to determine the effect of brain gym exercise on cognitive function in the elderly. This study employs an experimental research design. The sample used was 20 elderly who visited Puskesmas Tamalanrea Jaya Makassar. The sample was then divided randomly into two groups (intervention group and control group). Cognitive function in the elderly was measured using MMSE. The results showed that there were significant changes in cognitive function after the administration of brain gym in the intervention group (p 0.05). Moreover, it was found that there were no significant differences in cognitive function score between the two groups (p> 0.05). However, the average score of cognitive function in the intervention group is greater than in the control group. Therefore, it can be concluded that there is an effect of brain gym exercise on changes in cognitive function in the elderly.